2016
DOI: 10.1104/pp.16.01484
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod Affects the Phenotype of Mitochondrial Complex I Mutants

Abstract: Plant mutants for genes encoding subunits of mitochondrial complex I (CI; NADH:ubiquinone oxidoreductase), the first enzyme of the respiratory chain, display various phenotypes depending on growth conditions. Here, we examined the impact of photoperiod, a major environmental factor controlling plant development, on two Arabidopsis (Arabidopsis thaliana) CI mutants: a new insertion mutant interrupted in both ndufs8.1 and ndufs8.2 genes encoding the NDUFS8 subunit and the previously characterized ndufs4 CI mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 121 publications
(220 reference statements)
0
11
0
Order By: Relevance
“…The fact that respiratory CO 2 efflux is larger in some complex I mutants and not in others suggests that the lack of complex I activity alone is insufficient to stimulate catabolism and CO 2 efflux. Presumably, it depends on: (1) the actual reconfiguration of complex I (traces of complex I activity or the formation of subcomplexes; for a specific discussion, see Pétriacq et al ., ), (2) photorespiration; and (3) the units used to express respiration (typically the surface area or N content basis). Indeed, in the case of CMSII, which exhibited the larger respiration rate, both photorespiration (Fig.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The fact that respiratory CO 2 efflux is larger in some complex I mutants and not in others suggests that the lack of complex I activity alone is insufficient to stimulate catabolism and CO 2 efflux. Presumably, it depends on: (1) the actual reconfiguration of complex I (traces of complex I activity or the formation of subcomplexes; for a specific discussion, see Pétriacq et al ., ), (2) photorespiration; and (3) the units used to express respiration (typically the surface area or N content basis). Indeed, in the case of CMSII, which exhibited the larger respiration rate, both photorespiration (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…This is typically the case in both CMSII and NMS1 mutants ( R n larger than in WT; Fig. ; Sabar et al ., ; Priault et al ., ) and in the Arabidopsis mutant ndufs8 (same R n as in WT; Pétriacq et al ., ). In addition, we found here that the increase in day respiration ( R d ) was larger than that in R n , so that the inhibition of leaf respiration by light was lower in mutants than in WT.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In photosynthetic organisms, the NADH/NAD + status is known to regulate the coordination of nitrogen assimilation and carbon metabolism by various mechanisms (Dutilleul et al, 2005;Kämäräinen et al, 2017;Pétriacq et al, 2017). By applying a number of physiological measurements and the proteomics approach, we showed that the deletion of NdbC has a distinct effect on the metabolism of Synechocystis.…”
Section: Resultsmentioning
confidence: 99%